Immune Response to the Dual Antigen Vaccine of Actinobacillus pleuropneumoniae in a Mouse Model - Chuekwon, Kamonpun; Cheng, Li‑Ting (Trends in Sciences, 2023)
Actinobacillus pleuropneuminiae is the major cause of invasive respiratory disease in swine. To develop an efficient subunit vaccine against pathogens, we designed a dual antigen in a single vaccine that increased the potential for an immune response. We present a dual antigen vaccine (pore-forming domain and nutritional immunity) that induces humoral and cell-mediated T-cell responses, antibodies and TH1 and TH2 cells. Mice were immunized with the dual antigen and individual antigen and then subjected to immune response analysis. A significant antibody response was observed for the dual antigen group. For the cellular immune response, CD4+ and CD8+ T-cell expansion, proinflammatory cytokine (IL-1b, IL-6) and TH2-type cytokine (IL-4, IL-10) gene expression was observed for the dual antigen. Finally, in a challenge test with A. pleuropneumoniae serotype1, the dual antigen, individual antigen and PBS vaccine conferred 100, 40 and 0 % protection. In conclusion, the dual antigen presents critical antigens and increases the efficacy of the vaccine. HIGHLIGHTS The dual antigen vaccine of Actinobacillus pleuropneumonia (ApxII pore - forming domain and TonB2-the nutritional immunity antigen) were formulated as vaccines Mice were vaccinated, immune response analysis and challenge test were performed significant antibody response was observed and improved by approximately 2.5-fold for the dual antigen groups CD4 + and CD8 + T cell expansion was observed for the dual antigen group Protection rate of 100 %, 40 %, and 0 % was observed for the dual antigen, single antigen and negative control groups, respectively GRAPHICAL ABSTRACT